2013
DOI: 10.4236/ijaa.2013.33035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Space Radiations on the Nematode, <i> Caenorhabditis elegans </i>, through the Simulated Space Radiation

Abstract: In this study, we simulated space flight of the nematode, Caenorhabditis elegans, on the ground and examined how it is affected by space radiation and G-forces. We simulated G-forces during launch in a gravity acceleration laboratory device in order to identify and isolate the effects of the G-forces. Following this, we irradiated C. elegans with accelerated protons (MC-50 Cyclotron) and gamma rays (iR 222 machine) at the same physical dose. We calculated the expected radiation dose according to Reitz [1] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It is speculated that these changes on apoptosis result from interaction of environmental factors and genetic factors. Ground-based study has shown that apoptosis is reduced by protons but induced by γ-rays at the gene expression level during long-term spaceflight [ 76 ], indicating that the composition of complex types of space radiation may contribute to the perturbation of apoptosis. Environmentally, although the dose of space radiation is relative low in our study, the effect of space radiation can't be denied, because space radiation has been proven to induce obvious effects, even though the dose is three orders of magnitude lower than that of ground-based simulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that these changes on apoptosis result from interaction of environmental factors and genetic factors. Ground-based study has shown that apoptosis is reduced by protons but induced by γ-rays at the gene expression level during long-term spaceflight [ 76 ], indicating that the composition of complex types of space radiation may contribute to the perturbation of apoptosis. Environmentally, although the dose of space radiation is relative low in our study, the effect of space radiation can't be denied, because space radiation has been proven to induce obvious effects, even though the dose is three orders of magnitude lower than that of ground-based simulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the space-based experiments, numerous simulated ground-based radiation tests demonstrated the same changes observed during exposure in space. Yi et al performed a ground simulation on C. elegans where they simulated a long-duration flight and analyzed the effect of space radiation and gravitational force (G-force) on C. elegans [64]. In their experiment, they exposed C. elegans to accelerated protons and gamma rays with an equivalent dose.…”
Section: Space Vs Ground Experimentsmentioning
confidence: 99%
“…Dubois et al, 2019 [71] X-ray (600C/D linear accelerator) 0 gray [64], 200 Gy, and 400 Gy (not specified)…”
Section: Effect On Dna Responsementioning
confidence: 99%
“…In general, for a satellite assignment there are three levels of shock that are experienced: launching, separation from the rocket, and landing. Typical shock values experienced by previously reported missions are 4.5 G for the Russian Soyuz vehicle [ 32 ] and 3 G for NASA Space Shuttle [ 33 ]. To measure the level of shock, a finite element simulation (ANSYS 17.2) was performed with different shock levels.…”
Section: Device Characterization and Testingmentioning
confidence: 99%